Supramolecular Iron Complex Formed Between Nitrogen Riched Phenanthroline Derivative and Iron With Improved Oxygen Reduction Activity in Alkaline Electrolyte - Gu, Lin; Chu, Ya; Du, Hongmei; Zhang, Yan; Zhao, Jinsheng; Xie, Yu (Frontiers in Chemistry, 2019)
In this work, the synthesis and evaluation of a new type non noble metal oxygen reduction reaction (ORR) catalyst is reported. The catalyst is a complex containing iron ions and multiple N active sites, which displayed excellent oxygen reduction activity in alkaline medium. 2-(2-(4-(1H-imidazo[4,5-f][1,10]phenanthrolin-2-yl)pyridin-2-yl)pyridin-4-yl)-1H-imidazo[4,5-f][1,10]phenanthroline (PIPhen) was synthesized and used as a ligand to form a rich nitrogen iron coordination complex (Fe-PIPhen), and the complex was then loaded onto the carbon powder to form the target catalyst of Fe-PIPhen/C. The physical characterization of the catalyst was conducted by using Scanning Electron Microscopy (SEM), nitrogen adsorption-desorption and X-ray photoelectron spectroscopy (XPS), Brunauer-Emmett-Teller analysis etc. Electrochemical characterizations were realized by taking cyclic voltammetry (CV), linear sweep voltammetry (LSV) and rotating ring disk electrode (RRDE). The results show that Fe-PIPhen/C possesses the good performance; it exhibits a high electrocatalytic activity, which is mainly via a four electron ORR pathway, with a low hydrogen peroxide yield of 2.58%. And, the average electron transfer number of 3.93 was obtained in alkaline electrolyte. In summary, Fe-PIPhen/C will likely become a promising alternative to Pt catalyst in fuel cell.